Negotiated coexistence and environmental governance in protected nature areas of Peru - Mattias Borg Rasmussen (Íconos)
A central element in multi-scalar and hierarchical environmental governance is the provisional legitimacy of institutional arrangements. This article focuses on the strategies deployed by a sample of protected area managers in Peru in the work with, from, for and sometimes against communities in the search for a negotiated coexistence. Currently, the park-community relationship in Peru is characterized by a strategic approach. Based on interviews and government documents, this text analyzes the strategies and rationalities of environmental governance. An argument is developed about the consolidation of a social contract for conservation understood as the process that allows the establishment of reciprocal recognition between the protected area institution and local organizations. Three elements stand out in the interviews: the legacies of conservation in rural areas, the old and new spaces and mechanisms for participation, and the emergence of new forms of rural organization in relation to protected areas through the formalization of management agreements. It is concluded that each of these elements point to conditions for creating lasting legitimacy in conservation territories; however, these participatory and inclusive mechanisms are also hierarchical institutional spaces due to their emphasis on the creation of incentives.